2020
DOI: 10.18632/aging.202187
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine promotes recovery from oxidative stress and extends lifespan in C. elegans

Abstract: Carnitine is required for transporting fatty acids into the mitochondria for β-oxidation. Carnitine has been used as an energy supplement but the roles in improving health and delaying aging remain unclear. Here we show in C. elegans that L-carnitine improves recovery from oxidative stress and extends lifespan. L-carnitine promotes recovery from oxidative stress induced by paraquat or juglone and improves mobility and survival in response to H 2 O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…There has also been evidence of antioxidant defense dysregulation, as well as opposite relationships between antioxidant capacity and body fat percentage [11]. This could explain the reduced L-carnitine levels in obesity group in the present study, which may play a role in the loss of mitochondrial function since that L-carnitine have a role in the recovery from OS [22].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…There has also been evidence of antioxidant defense dysregulation, as well as opposite relationships between antioxidant capacity and body fat percentage [11]. This could explain the reduced L-carnitine levels in obesity group in the present study, which may play a role in the loss of mitochondrial function since that L-carnitine have a role in the recovery from OS [22].…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, this study found that serum levels of L-carnitine have significantly reduced in children with obesity. The recovery of L-carnitine in OS might be important for health [22].…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid metabolic disorder in MTKO mice may have led to high-fat diet-induced fatty liver and obesity [ 66 ] and a shortened lifespan [ 20 ]. Carnitine protects from oxidative stress and extends the lifespan of C. elegans [ 67 ]. Older MTKO mice with low L-carnitine plasma levels may be vulnerable to oxidative stress enhanced by the deficiency of MT, as MT is an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…[ 177 ] The GPS‐induced extension of RLS was abolished in a strain lacking ATG32 , a gene required for mitophagy, and RLS extension by GPS may therefore depend on mitophagy. [ 178 ] However, CLS extension also occurs in Δ atg32 cells, so mitophagy may be not involved in CLS extension by GPS. [ 165 ]…”
Section: Low‐molecular Weight Compounds That Extend the Chronological...mentioning
confidence: 99%